The Role of Coastal Women’s Empowerment in Achieving The Success of SDGs: A Study on The Kebaya Group, Bekasi - Rahadiyand Aditya; Suryo Ediyono; Sugihardjo Sugihardjo (Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
Land conversion has occurred in the coastal area of Kampung Beting, Pantai Bahagia Village, Bekasi Regency. What used to be a mangrove plantation has transformed into spaces for fish and shrimp ponds. This phenomenon took place from 2001 to the early 2010s. The promise of lucrative income led the community to compete in changing land use without considering the potential consequences. After 2011, the community gradually began to feel the negative impacts of this land conversion. To this day, the entire area that was once used for ponds has turned into the sea, causing the community to lose their livelihoods. Furthermore, not only have they lost their livelihoods, but they have also been confronted with land degradation, which threatens their sustainability. This study examines how coastal women's empowerment activities can contribute to sustainable development. The research employs a phenomenological approach, and data is collected through observation, interviews, and documentation. The findings indicate that Coastal Women's Empowerment Contributes to Sustainable Goals in Climate Change Mitigation, Gender Equality, and Poverty Alleviation. In climate change mitigation activities, there are two key activities: 1) the development of women's behavior in efforts to improve and rehabilitate critical lands, and 2) women's involvement in the maintenance of mangrove trees. In gender equality activities, there is one main activity: 1) active participation of women in productive economic activities, allowing coastal women in Pantai Bahagia Village to have regular activities beyond their domestic responsibilities. The focus of poverty alleviation activities is 2) increasing income by utilizing non-timber mangrove products for food processing and crafts.